MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA DENGAN MENGGUNAKAN METODE PEMECAHAN MASALAH DI KELAS IV SD 107400 B. KHALIPAH TAHUN AJARAN 2020-2021 - Salome Tampubolon; Fahmi Ashari S Sihaloho; Vivi Uvaira Hasibuan (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2022)
The learning outcomes of fourth graders at SD Negeri 107400 B.Khalipah in mathematics subjects with the addition and subtraction of decimal fractions for the 2020/2021 school year are still low. To achieve optimal results, teachers need to use learning methods that can help students, namely by using solving methods. problem. This study used a classroom action research design which was carried out in two cycles. The subjects in the study were fourth grade students of SD Negeri 107400 B.Khalipah for the academic year 2020/2021, totaling 36 students. Data collection techniques were carried out through test and non-test (questionnaire, observation and documentation). The results showed an increase in teacher performance, activity, motivation and student learning outcomes in the first cycle to the second cycle. In the first cycle the teacher's performance value was 81.69% and increased in the second cycle to 88.54%, the average value of student learning activities in the first cycle was 75.98% and in the second cycle was 88.80%, the average value students' learning motivation in the first cycle is 75.85%. Based on these results, it can be concluded that the problem solving method can improve student learning outcomes in mathematics subjects in the material of decimal fractions in class IV SD Negeri 107400 B.Khalipah.